2022
DOI: 10.1101/2022.03.17.22272498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remote virtual reality assessment elucidates self-blame-related action tendencies in depression

Abstract: Darwin stated that humans have a strong and involuntary tendency to perform certain actions when a specific state of mind is induced. Such "action tendencies" are key to understanding the maladaptive impact of self-blame-related feelings in depression. For example, feeling like "hiding" and "creating a distance from oneself" in a text-based task were previously associated with recurrence risk in remitted depression. Despite their functional importance, action tendencies have not been systematically investigate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…In line with this, Tangney et al (2007) postulated that adaptive self-blame-related action tendencies are more associated with behavioural activation and involve proactive pursuit such as reparative actions, whereas maladaptive self-blame-related action tendencies motivate social withdrawal and interpersonal separation (Duan, Lawrence, et al, 2022; Tangney et al, 2007). In keeping with this hypothesis, using a text-based task, we recently showed that withdrawal-related maladaptive action tendencies including hiding and creating a distance from oneself were more pronounced in patients with remitted depression compared with control participants (Duan, Lawrence, et al, 2022) and were associated with subsequent recurrence risk (Duan, Lawrence, et al, 2022; Duan, Valmaggia, et al, 2022).…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…In line with this, Tangney et al (2007) postulated that adaptive self-blame-related action tendencies are more associated with behavioural activation and involve proactive pursuit such as reparative actions, whereas maladaptive self-blame-related action tendencies motivate social withdrawal and interpersonal separation (Duan, Lawrence, et al, 2022; Tangney et al, 2007). In keeping with this hypothesis, using a text-based task, we recently showed that withdrawal-related maladaptive action tendencies including hiding and creating a distance from oneself were more pronounced in patients with remitted depression compared with control participants (Duan, Lawrence, et al, 2022) and were associated with subsequent recurrence risk (Duan, Lawrence, et al, 2022; Duan, Valmaggia, et al, 2022).…”
Section: Introductionmentioning
confidence: 83%
“…Exclusion criteria were: a previously diagnosed or likely bipolar disorder [Hypomanic Checklist-16 (Forty et al, 2010) score > 8, with symptoms lasting ≥ 2 days, and endorsing two of the first three screening questions of the Composite International Diagnostic Interview bipolar screening scale (Kessler et al, 2006)], a personal history of schizophreniform symptoms [three clinical screening questions to exclude schizophreniform disorders (Lythe et al, 2015)], drug or alcohol abuse over the last 6 months [Primary Care Evaluation of Mental Disorders (Spitzer et al, 1994), modified to screen for drug abuse], a suspected central neurological condition, a planned or current pregnancy, or currently being treated by a mental health specialist in secondary care. More information about the inclusion/exclusion reasons can be found in the Supplementary Materials of Duan, Valmaggia, et al (2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations